The potential scalability of salt substitutes as an intervention to lower population sodium levels - Antonio Bernabe-Ortiz; Kathy Trieu; Matti Markland; Jason HY Wu; Lorena Saavedra-Garcia; Ashleigh C Hart; Jie Yu; Sudhir Raj Thout; J Jaime Miranda; Jacqui Webster (Salud Pública de México, 2022)
Reducing salt intake is one of the most cost-effective interventions to improve population health due to the subsequent reductions in blood pressure. Countries are introducing programs to lower salt consumption. Such programs usually focus on reducing salt in packaged foods and meals alongside campaigns to change consumer behavior. Thus, this paper provides an overview of the rationale for and evidence supporting the use of salt substitutes. Current approaches to salt reduction are insufficient, and more innovative solutions need to be identified. There is good evidence that salt substitutes, where some of the sodium is replaced with potassium, are effective to lower sodium total intake. The main challenge is to understand the pathways to market for salt substitutes. How do we implement programs to promote salt substitutes in different countries? What levels of government intervention are required? With more research and government investment, salt substitutes could be a game changer for increasing the impact of strategies to reduce population salt intake.